Attitude of Generations : Does It Matter Online ? - Thomas, Mary Rani; Mathew, Jain (Indian Journal of Marketing, 2021)
Generational examinations are turning out to be necessary with the characteristics they exhibit. This research work aimed at establishing the interceding relationship of disposition of three distinctive generations - Generation X, Generation Y, and Generation Z. In complete, 1200 responses were acquired from both male and female respondents of each generational class dependent on online purchase data collected by employing Google Forms. For the investigation, the model utilized the SOR framework. The results indicated that attitude does not play a vital role in the purchase intention of Generation X followed by the partial mediation of attitude for Generation Y and full mediation effect for Generation Z. This steady increment of attitudinal change underpins the examination by setting up proof that every age shifts in their mentality and purchasing conduct. Online retailers must concentrate on showcasing systems and create online visual merchandising cues which outwardly advance and make a feeling of stimulating attitude for generations. The current study also added value to the existing literature by classifying the customer base not merely on age, but also on their technological perspective of distinguishing web atmospheric cues and catering to their needs from a generational outlook. The study also took into account the importance of the organism’s role played by attitude in the S-O-R framework. In this manner, the study helps marketers to design methodologies and plan online visual marketing space for better generational reaction and benefit.